2013
DOI: 10.1142/8804
|View full text |Cite
|
Sign up to set email alerts
|

Hilbert–Huang Transform and Its Applications

Abstract: The Hilbert-Huang transform and its applications / editors, Norden E. Huang, Samuel S.P. Shen. p. cm.-(Interdisciplinary mathematical sciences ; v. 5) Includes bibliographical references and index. ISBN 981-256-376-8 (alk. paper) 1. Hilbert-Huang transform. 2. Decomposition (Mathematics) I. Huang, N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
365
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(367 citation statements)
references
References 0 publications
0
365
0
2
Order By: Relevance
“…Reynolds-dependent) intermittent corrections. Other analysing tools which have proved to be optimal to reduce non-local effects, such as the Hilbert-Huang transform (Huang & Shen 2005), may also help to better clarify this point. If intermittency in the helical cascade is confirmed, it will be important to study it in a more quantitative way in order to understand similarities to and differences from the corresponding phenomenon observed for the whole NS dynamics with all triads included and in the presence of rotation (Mininni et al 2009).…”
Section: Direct Helicity Cascadementioning
confidence: 99%
“…Reynolds-dependent) intermittent corrections. Other analysing tools which have proved to be optimal to reduce non-local effects, such as the Hilbert-Huang transform (Huang & Shen 2005), may also help to better clarify this point. If intermittency in the helical cascade is confirmed, it will be important to study it in a more quantitative way in order to understand similarities to and differences from the corresponding phenomenon observed for the whole NS dynamics with all triads included and in the presence of rotation (Mininni et al 2009).…”
Section: Direct Helicity Cascadementioning
confidence: 99%
“…As expected, each consecutive IMF had characteristically lower frequencies. It can also be observed that, although a summation of the IMFs and the residue results in the input signal, the IMFs and the residue extracted do not have the slightest propensity towards linearity, stationarity nor time-invariance (Echeverria et al, 2001;Huang and Shen, 2005;Shi and Law, 2007). This approach to signal decomposition is effectively dynamic and is void of a priori assumptions of the characteristics of the input data.…”
Section: Signal Decomposition and Noise Extractionmentioning
confidence: 99%
“…Empirical mode decomposition (EMD) [1] is a technique specially developed for analyzing various kinds of non-stationary signals. Its uniqueness, power and effectiveness have already been demonstrated by its successful applications to many important problems encountered in processing biomedical, financial, geographical, acoustic, vibrational, hydroacoustic and other types of signals.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the IMF extraction is terminated and a final monotonous residual is formed. The two necessary conditions a function must satisfy in order to be counted as an IMF are as follows [1]:…”
Section: Introductionmentioning
confidence: 99%